Muslim refugees, the forgotten people in Sri Lanka's ethnic conflict - Hasbullah, S. H.; Research and Action Forum for Social Development (Sri Lanka) (Nuraicholai, Sri Lanka : Research and Action Forum for Social Development, 2001)
Study related to Northern Provinces in Sri Lanka.
Keywords: Muslims -- Sri Lanka -- Northern Provinces -- Economic conditions; Muslims -- Sri Lanka -- Northern Provinces -- Social conditions; Northern Provinces (Sri Lanka) -- Economic conditions; Northern Provinces (Sri Lanka) -- Social conditions